Minimum Price Guarantees In a Consumer Search Model - Maarten Janssen; Alexei Parakhonyak (Tinbergen Institute, 2009)
This paper is the first to examine the effect of minimum price guaranteesin a sequential search model. Minimum price guarantees are notadvertised and only known to consumers when they come to the shop.We show that in such an environment, minimum price guarantees increasethe value of buying the good and therefore increase consumers' reservationprices. This increase is so large that even after accounting for thefact that some consumers will buy at lower prices, firms profits are largerunder minimum price guarantees than without it. We also show that anequilibrium where all firms offer minimum price guarantees does not existbecause of a free-riding problem. Minimum price guarantees can onlybe an equilibrium phenomenon in an equilibrium where firms randomizetheir decision to offer these guarantees.
Keywords: D40; D83; L13; 330; Sequential Search; Minimum Price Guarantees; Welfare Analysis; Preismanagement; Konsumentenverhalten; Suchtheorie; Wohlfahrtsanalyse; Theorie